Pengaruh Kualitas Pelayanan Publik terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan ( Studi di Kecamatan Remboken Kabupaten Minahasa) - Tesalonika Vinolla Jeanneta Tompodung; Florence D. J. Lengkong; Very Y. Londa (Sam Ratulangi University, 2023)
One of the high and low compliance of taxpayers is influenced by the quality of service. The better the quality of service, the higher the level of taxpayer compliance. The purpose of this study was to find out how much influence the quality of public services has on the compliance of land and building taxpayers. The research method used is a quantitative research method. The sample in this research is the people in Remboken District who are registered as Land and Building Taxpayers with 100 respondents. The results obtained, namely the Quality of Public Services has a positive effect on Land and Building Taxpayer Compliance as indicated by the regression equation Y = 36.417 + 0.804X and hypothesis testing with the t-test which shows the value of t count = 3.023 more than the value of t table = 1.984 with Sig level 0.016 <0.05 so that H0 is rejected and Ha is accepted. The magnitude of the influence is indicated by the coefficient of determination of 0.616, which means that the influence of the Quality of Public Services on Compliance with Land and Building Taxpayers is 61.6%.